2019
DOI: 10.1038/s42004-019-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

Niobium pentoxide nanomaterials with distorted structures as efficient acid catalysts

Abstract: Niobium pentoxides are promising acid catalysts for the conversion of biomass into fuels and chemicals. Developing new synthesis routes is essential for designing niobium pentoxide catalysts with improved activity for specific practical processes. Here we show a synthesis approach in acetophenone, which produces nanostructured niobium pentoxides with varying structure and acidity that act as efficient acid catalysts. The oxides have orthorhombic structures with different extents of distortions and coordinative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 59 publications
8
51
0
Order By: Relevance
“…For example, in 1973 IIjima showed the presence of blocks of different sizes assigned as heavily disordered regions in the H-Nb2O5, 54 and several studies conducted in the 1970s show similar imperfections in the block structure of Nb2O5. [55][56][57] More recently, Russo et al 8 showed that T-Nb2O5 nanoparticles synthesized through solvothermal synthesis with NbCl5 and acetophenone have regions deviating from the crystalline nature of the material. Figure 4 shows an illustration of the type the expected defects found in niobium oxide particles compared to the idealized H-Nb2O5 structure.…”
Section: Fig 2 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 1973 IIjima showed the presence of blocks of different sizes assigned as heavily disordered regions in the H-Nb2O5, 54 and several studies conducted in the 1970s show similar imperfections in the block structure of Nb2O5. [55][56][57] More recently, Russo et al 8 showed that T-Nb2O5 nanoparticles synthesized through solvothermal synthesis with NbCl5 and acetophenone have regions deviating from the crystalline nature of the material. Figure 4 shows an illustration of the type the expected defects found in niobium oxide particles compared to the idealized H-Nb2O5 structure.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…fuels and chemicals from biomass sources. [8][9][10] Niobium oxides have furthermore been extensively studied for their electrochromic properties e.g. photodetection 11 and in recent years, the potential of amorphous and nanostructured Nb2O5 for electrochromic windows has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…42 The high-resolution C 1s spectra of the as-fabricated N-NBO/C were deconvoluted into four peaks at 284.2, 284.8, 286 and 288 eV. The two peaks at 284.2 and 284.8 eV are ascribed to adventitious carbon (C-C/C]C), 43 which was created owing to the incomplete burning of the organic constituent and pollution from the air, and the peaks at around 286 eV and 288 eV are ascribed to the existence of C-O and O-C]O groups, 34,35 respectively. The carbon in N-NBO/C is attributed to CO X species from the incomplete thermal decomposition of the organic component (Hmta) adsorbed on the surface of NBO aer the heat treatment.…”
Section: Morphology and Structure Of The Photocatalystsmentioning
confidence: 99%
“…The representative fit of the O1s region of Nb 2 O 5 _550_air is shown in Figure 2 . As can be seen in this result, the high resolution O1s XPS region was deconvoluted into three different species, namely O (I) with BE of 529.80–530.59 eV, assigned to lattice oxygen (O 2- ) in metal oxide, O (II) with BE of 530.87–531.63 eV [ 42 , 52 ], corresponding to oxygen in CO and OH [ 52 , 54 ], and O (III) with BE of 531.97–532.83 eV [ 47 , 54 ] attributed to physically adsorbed water. It is noted that the C-O interactions probably originated from the presence of adventitious carbon in all samples, as previously mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the XPS Nb3d regions of Nb 2 O 5 _SA and Nb 2 O 5 _550_air can be found in Figure 3 . The high-resolution core level XPS spectra of Nb3d, due to spin-orbit splitting, showed two photoelectron peaks (Nb3d 5/2 and Nb3d 3/2 ) with BE in the range of 206–207 eV and 209–210 eV, corresponding to Nb 2 O 5 [ 54 ]. Moreover, a higher BE of the core level of the Nb3d main peak (Nb3d 5/2 ) was recorded for the amorphous samples, and the BE values decreased with increasing crystallinity of the materials, as evidenced in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%